Psychological factors predicting social distance during the COVID-19 pandemic: an empirical investigation - Lo Destro, Calogero (Psychology Hub, 2022)
Numerous nations around the world are facing exceptional challenges in employing measures to stop the spread of COVID-19. Following the recommendations of the World Health Organization, a series of preventive measure have been adopted. However, individuals must comply with these rules and recommendations in order to make such measures effective. While COVID-19 was climaxing, it seemed of crucial importance to analyze which psychosocial factors contribute to the acceptance of preventive behavior, thus favoring the management of COVID-19 worldwide health crisis. In particular, the identification of aspects related to obstacles and facilitations of adherence to social distancing has been considered as crucial in the containment of the virus spread. We hypothesized social distance could be influenced by individual psychological differences and target’s characteristics. Specifically, since the virus was firstly detected in China, we assumed Asian people could be considered a relevant outgroup targeted for exclusion. 260 participants participated in this research on a voluntary basis. They filled a survey designed to explore a series of COVID-19 measures (such as exposure to virus and fear of infection). Participants’ state and trait anxiety was also assessed. The dependent variable was social distance, based on a measure of seating distance, designed ad hoc for the present study. Our hypothesis that participants could reports greater distance in response to Asian people was not confirmed. On the other hand, significantly lower distance in response to smiling compared to coughing targets was displayed. Finally, adopting a regression analysis model, we found that participants’ social distance, in response to both coughing and smiling targets was predicted by fear of infection and by the perception COVID-19 could become a pandemic. Social distance in response to coughing target was also significantly and positively predicted by age and state anxiety. In summary, the present work has sought to identify a set of psychological variables, which may still be relevant in predicting social distancing.